Theoretical and experimental study of the bending collapse of partially reinforced CFRP–Steel square tubes - Lavayen-Farfan, D.; Butenegro-Garcia, J.A.; Boada, M.J.L.; Martinez-Casanova, M.A.; Rodriguez-Hernandez, J. (Elsevier, 2022)
Bending collapse of thin-walled steel tubes is a major energy absorption mechanism in lightweight structures, especially for crashworthiness. External composite reinforcements can increase the energy absorption and strength of steel tubes. However, to this date there are still difficulties to determine the maximum load and the collapse behavior of reinforced, multi-material shapes, e.g., steel shapes covered by CFRP. In this work, a theoretical analysis of the collapse of a partially reinforced CFRP–Steel tube is performed, which encompasses the calculation of both the peak bending moment and the bending collapse curve of tubes with either the flanges or webs with reinforcements. The theoretical approach is validated with three-point bending experimental tests and an adequate agreement with experiments is found. The results also show an important increase of up to 57% in the peak load and 45% in the specific energy absorbed for partially reinforced tubes, with a maximum 14% increase in weight, when compared with unreinforced tubes. The developed theoretical model enhances even further the existing bending collapse theories, as it incorporates reinforcements in the model and provides a powerful tool for engineering analyses, and can be implemented in concept models, and optimization algorithms with ease. These findings can be used for enhancing existing and new lightweight structures and improving the crashworthiness of several automotive structures.
Keywords: Crashworthiness; Bending; Structural engineering; Materials science; Bending moment; Reinforcement; Composite material; Tube (container); Finite element method; Engineering; https://purl.org/pe-repo/ocde/ford#2.01.02